Family Christmas at Kinswomen - Watkins, Howard::::::::: (1988)
Christine Watkins, Jerry Kamp, Adam Watkins, Robin Watkins, Albert Watkins, Rose O'Reilly, Frances Kamp, and Howard Watkins Stereo component set in cabinet